A Note on Arthraxon microphyllus (Trin.) Hochst. (Poaceae) - Jain, S. K. (Indian Forester, 1971)
Arthraxon microphyllus (Trin.) Hoehst. Is different from A. lencifolius trin.) Hochst. A. sikkimensis Bor is synonymous with A. microphyllus.